2018
DOI: 10.1371/journal.pone.0199827
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of HIF-1-responsive microRNA210/HIF3 axis on gemcitabine resistance in cholangiocarcinoma cells

Abstract: MicroRNA-210 (miR-210) is a robust target for hypoxia-inducible factor, and its overexpression has been detected in a variety of solid tumors. However, the role of miR-210 in the development, progression and response to therapy in cholangiocarcinoma (CCA) remains undefined. We report here that high miR-210 expression was significantly correlated with the shorter survival of CCA patients. Overexpression of miR-210 inhibited CCA cell proliferation at the G2/M phase and reduced the gemcitabine sensitivity in CCA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Previous research reported that HIF-1α can regulate transcription of multiple miRNAs in hypoxia (29). The study by Silakit et al indicated that miR-210 acted as downstream of HIF-1α and was upregulated in various cancer cells under hypoxia condition (30). The research by Guo et al demonstrated that miR-224-3p was one of the downregulated miRNAs in glioblastoma cells under hypoxia (31).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research reported that HIF-1α can regulate transcription of multiple miRNAs in hypoxia (29). The study by Silakit et al indicated that miR-210 acted as downstream of HIF-1α and was upregulated in various cancer cells under hypoxia condition (30). The research by Guo et al demonstrated that miR-224-3p was one of the downregulated miRNAs in glioblastoma cells under hypoxia (31).…”
Section: Discussionmentioning
confidence: 99%
“…Increased miR-210 expression in CCA tissues was shown, compared with normal bile duct tissues, and associated with shorter survival [ 26 ]. In a pseudohypoxia status induced by CoCl 2 treatment, miR-210 suppressed the proliferation of malignant cholangiocytes through increasing cell cycle arrest at G2/M phase [ 26 ]. Furthermore, miR-210 decreased gemcitabine sensitivity by targeting HIF-3α, a negative regulator of HIF-1α.…”
Section: Mirnas and Resistance To Gemcitabinementioning
confidence: 99%
“…Furthermore, miR-210 decreased gemcitabine sensitivity by targeting HIF-3α, a negative regulator of HIF-1α. Overall, Silakit et al demonstrated that the positive feedback loop of miR-210/HIF-1α, by regulating HIF-3α, may contribute to cell arrest and gemcitabine resistance of CCA under hypoxia [ 26 ].…”
Section: Mirnas and Resistance To Gemcitabinementioning
confidence: 99%
“…MiR-210 is upregulated by hypoxia in most of solid tumors and targets genes involved in cell cycle regulation, cell survival, differentiation, angiogenesis, metabolism and cancer cell immune evasion [103]. This miRNA is considered a master hypox-amiR and a new biomarker of metastatic potential and chemoresistance in different solid tumors [104][105][106].…”
Section: Micrornasmentioning
confidence: 99%